CSF neopterin and quinolinic acid are biomarkers of neuroinflammation and neurotoxicity in FIRES and other infection‐triggered encephalopathy syndromes - Russell C. Dale; Terrence Thomas; Shrujna Patel; Velda X. Han; Kavitha Kothur; Christopher Troedson; Sachin Gupta; Deepak Gill; Stephen Malone; Michaela Waak; Sophie Calvert; Gopinath Subramanian; et al. (Annals of Clinical and Translational Neurology, 2023)
Abstract Objective Infection‐triggered encephalopathy syndromes (ITES) are potentially devastating neuroinflammatory conditions. Although some ITES syndromes have recognisable MRI neuroimaging phenotypes, there are otherwise few biomarkers of disease. Early detection to enable immune modulatory treatments could improve outcomes. Methods We measured CSF neopterin, quinolinic acid, kynurenine and kynurenine/tryptophan ratio using a liquid chromatography coupled to tandem mass spectrometry (LC–MS/MS) system. The CSF of 18 children with ITES were compared with acute encephalitis (n = 20), and three control groups, namely epilepsy (n = 20), status epilepticus (n = 18) and neurogenetic controls (n = 20). Results The main ITES phenotypes in 18 patients were acute encephalopathy with biphasic seizures and late restricted diffusion (AESD, n = 4), febrile infection‐related epilepsy syndrome (FIRES n = 4) and other ITES phenotypes. Influenza A was the most common infectious trigger (n = 5), and 50% of patients had a preceding notable neurodevelopmental or family history. CSF neopterin, quinolinic acid and kynurenine were elevated in ITES group compared to the three control groups (all p < 0.0002). The ROC (area under curve) for CSF neopterin (99.3%, CI 98.1–100) was significantly better than CSF pleocytosis (87.3% CI 76.4–98.2) (p = 0.028). Elevated CSF neopterin could discriminate ITES from other causes of seizures, status epilepticus and febrile status epilepticus (all p < 0.0002). The elevated CSF metabolites normalised during longitudinal testing in two patients with FIRES. Interpretation CSF neopterin and quinolinic acid are neuroinflammatory and excitotoxic metabolites. This CSF metabolomic inflammatory panel can discriminate ITES from other causes of new onset seizures or status epilepticus, and rapid results (4 h) may facilitate early immune modulatory therapy.